2021
DOI: 10.2166/ws.2021.387
|View full text |Cite
|
Sign up to set email alerts
|

Study on applicability of remote sensing precipitation products in hilly-plain-wetland complex area of northeast China

Abstract: For the hilly-plain-wetland complex ecosystem in the cold region of Northeast China, in order to solve the problems, which include the scarcity of surface rainfall stations and the inability to provide accurate surface precipitation for hydrological process simulation, based on the observed precipitation of rainfall stations, three remote sensing precipitation products are taken as objects of evaluation. They include TRMM (Tropical Rainfall Measuring Mission) 3B42V7,3B42RT and CHIRPS (Climate Hazards Group Inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Then, the flood routing distribution maps were generated (Figure 8), in order to adequately visualize the flow ranges obtained for the return periods of 5 years (Figure 8a), 25 years (Figure 8b), 50 years (Figure 8c) and 100 years (Figure 8d). An interpolation method based on inverse distance weighting (IDW) was used for this analysis (Wang et al, 2022). This IDW technique is appropriate when there is a need to quantify values in areas where data are not available, as it correlates them with stations that do have complete values, much wider ranges of the meteorological variable under study can be obtained (Arriola et al, 2022;Tan et al, 2021;Vargas et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Then, the flood routing distribution maps were generated (Figure 8), in order to adequately visualize the flow ranges obtained for the return periods of 5 years (Figure 8a), 25 years (Figure 8b), 50 years (Figure 8c) and 100 years (Figure 8d). An interpolation method based on inverse distance weighting (IDW) was used for this analysis (Wang et al, 2022). This IDW technique is appropriate when there is a need to quantify values in areas where data are not available, as it correlates them with stations that do have complete values, much wider ranges of the meteorological variable under study can be obtained (Arriola et al, 2022;Tan et al, 2021;Vargas et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…In future studies, hydrological data from 2015 to 2022 will also be considered using another product. evaluated the applicability of monthly precipitation data from the GLDAS-2.0 in China, and the results proved that the GLDAS-2.0 rainfall data used in study have good consistency and data quality, and good applicability [39]. also evaluated the applicability of hydrological products of the GLDAS Noah model in China, and the results showed that the quality of the hydrological products of the GLDAS-2.0 is higher than that of the GLDAS-1.0, and the runoff products of the GLDAS-2.0 have better applicability and can be applied to the relevant research in China [40].…”
Section: Data Sourcesmentioning
confidence: 92%
“…At present, the integration of spatial information technology with RS and GIS as the core of hydrodynamic simulation has been fully applied to land spatial planning, flood control and waterlogging drainage and other special ecological security planning. Swat, HEC-HMS, Xin'anjiang model and other models have been applied to the study of watershed simulation and have obtained rich research results [7][8][9] The SCS model proposed by the soil conservation agency of the United States Department of agriculture includes two modules of runoff generation and confluence [10] , which summarizes the impact and contribution of many environmental factors into a spatial parameter (CN value [11] ). The calibration of SCS model is relatively easy and reliable [12] , and previous studies have accumulated [13] , which has high runoff simulation accuracy in small watersheds [14] .…”
Section: Research Methods and Technical Routesmentioning
confidence: 99%